POTENSI HAK EKSEKUTORIAL BAGI KREDITUR DALAM PERJANJIAN FIDUSIA - Jhoni Jhoni; Meirina Dewi Pratiwi (Fakultas Hukum Universitas IBA Palembang, 2020)
ABSTRACT The Fiduciary Guarantee makes it easy for those who use it. However, in the current practice, there are several violations of law committed by debtors and creditors, for example, there are still creditors who do not register fiduciary deeds to fiduciary registration offices, debtors who transfer, mortgage, and lease fiduciary collateral objects without the creditor's permission and others. -other. From the problems above, of course there must be a solution for Debtors and Creditors. The creditor must really understand the tendency of the debtor as the fiduciary giver, and must follow the mandate of the law in order to register the fiduciary deed made before a notary public and register it with the Ministry of Law and Human Rights so that when something unexpected happens, the creditor has permanent legal force.